2018
DOI: 10.5194/hess-22-1119-2018
|View full text |Cite
|
Sign up to set email alerts
|

A global approach to estimate irrigated areas – a comparison between different data and statistics

Abstract: Abstract. Agriculture is the largest global consumer of water. Irrigated areas constitute 40 % of the total area used for agricultural production (FAO, 2014a) Information on their spatial distribution is highly relevant for regional water management and food security. Spatial information on irrigation is highly important for policy and decision makers, who are facing the transition towards more efficient sustainable agriculture. However, the mapping of irrigated areas still represents a challenge for land use … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
144
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 161 publications
(149 citation statements)
references
References 37 publications
2
144
2
1
Order By: Relevance
“…Meier et al. () observes that, globally, official institutions might underestimate irrigated areas by 22%, with some regions in Africa and Asia having irrigated areas that are >10 3 times larger than those reported by the Food and Agriculture Organization (FAO).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meier et al. () observes that, globally, official institutions might underestimate irrigated areas by 22%, with some regions in Africa and Asia having irrigated areas that are >10 3 times larger than those reported by the Food and Agriculture Organization (FAO).…”
Section: Methodsmentioning
confidence: 99%
“…In the case of irrigation agriculture, the discrepancies are large: the irrigated areas attested by Thenkabail et al (2009b) for India are 40% larger than those reported by the Indian Ministry of Water. Meier et al (2018) observes that, globally, official institutions might underestimate irrigated areas by 22%, with some regions in Africa and Asia having irrigated areas that are >10 3 times larger than those reported by the Food and Agriculture Organization (FAO).…”
Section: The Data Setsmentioning
confidence: 95%
“…Meier et al . () mapped the irrigated agriculture by integrating RS and GMIA and marked missing areas in India mainly situated within densely irrigated regions already present in the statistics. They found the absence of minor irrigation practices from statistics responsible for this (e.g.…”
Section: Irrigated Areas’ Reporting Methodologiesmentioning
confidence: 99%
“…In these regions, under-reporting of irrigated land belonging to small and marginal farmers is likely to occur as the majority of these farmers buy water and do not own pumps, and thus could be overlooked during minor irrigation enumeration (Srivastava and Kumar, 2007;Kumar et al, 2013). Meier et al (2018) mapped the irrigated agriculture by integrating RS and GMIA and marked missing areas in India mainly situated within densely irrigated regions already present in the statistics. They found the absence of minor irrigation practices from statistics responsible for this (e.g.…”
Section: Chinamentioning
confidence: 99%
See 1 more Smart Citation